Pencemaran Parasit Pada Sayuran di Beberapa Pasar Tradisional Kota Malang - Permata Ika Hidayati; As'ad Syamsul Arifin; Dyah Ayu Widyaningrum (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2022)
Vegetables have been reported as a mechanical means of transmission of human intestinal parasites. This study aims to determine the relationship between parasites and vegetables sold in Malang City. Two hundred and fifty (250) vegetables were subjected to sedimentation and zinc sulfate flotation techniques for parasite investigations. Results: Of the 250 vegetables examined, 184 (68.15%) were infected. T. occidentalis had the highest prevalence (9.26%), followed by B. oleracea and D. carota with respective values ​​of 8.89% and 8.15%. The highest parasite prevalence was observed in Pasar Besar (78.89%), followed by Mergan Market (72.22%) and Dinoyo Market (53.33%). Pasar Besar has the highest prevalence of D. carota and C. sativum with a prevalence of 11.11 and 10.00%, respectively. Statistically, there were no significant differences in contaminated vegetables (p > 0.05) but significant differences were seen at market locations (p < 0.05). The highest percentage of parasite occurrence was A. lumbricoides with an occurrence percentage of 23.49. The most common parasites in the Big Market are Ascaris lumbricoides (45.56%) and Entamoeba histolytica (30.00%). There was a significant effect (p < 0.05) on parasite prevalence (p = 0.0003; df = 6; F = 11.07) and market location (p = 0.0019; df = 2; F = 11.01 ). Main component analysis shows that the location of the study has a positive effect on the incidence of parasites with the Big Market location of 95.99% of the total variance. Further analysis showed that A. lumbricoides , Trichuris trichura , and hookworm prevalence were strongly correlated with the location of Pasar Besar and Pasar Dinoyo. Given the public health importance of isolated parasites, there is a need to improve environmental sanitation, personal hygiene and surveillance systems in vegetable transportation, storage and display facilities in Malang City in general.